2020
DOI: 10.1111/joop.12322
|View full text |Cite
|
Sign up to set email alerts
|

A test of work motivation profile similarity across four distinct samples of employees

Abstract: The present study examines how the different forms of behavioural regulation proposed by self‐determination theory combine within different profiles of workers and the extent to which these configurations are replicated among four samples of workers from distinct occupational groups (managers, nurses, physiotherapists, and hospital employees). In addition, this research investigates the role of workload (as a job demand), as well as perceived organizational, supervisor, and colleagues support (as job resources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 121 publications
4
22
0
Order By: Relevance
“…Indeed, it is noteworthy that, as in prior research (Gillet, Morin, et al, 2020;Rainbow, 2019), presenteeism was associated with *p = .055;; **p < .01.…”
Section: Theoretical Implicationssupporting
confidence: 53%
See 2 more Smart Citations
“…Indeed, it is noteworthy that, as in prior research (Gillet, Morin, et al, 2020;Rainbow, 2019), presenteeism was associated with *p = .055;; **p < .01.…”
Section: Theoretical Implicationssupporting
confidence: 53%
“…Contrary to workaholism (Balducci et al, 2020;Gorgievski et al, 2010), presenteeism which is considered to be more transitory and situational (George et al, 2017) has been found to be constantly associated with lower levels of work performance (Gillet et al, 2020b;Miraglia & Johns, 2016), especially in the nursing profession (Li et al, 2019;Rainbow, 2019). This may be explained by higher anxiety (Monzani et al, 2018) or lower psychological health (Li et al, 2019).…”
Section: Background the Negative Outcomes Of Workaholism And Presenteeismmentioning
confidence: 98%
See 1 more Smart Citation
“…Authors divided hospital employees into four groups (managers, nurses, rehabilitation specialists and hospital employees). The results indicated that training courses have the greatest impact on the motivation of managers, followed by rehabilitation specialists, then hospital workers and nurses in the last position [11]. The analysis continues SHS Web of Conferences 92, 0 (2021) Globalization and its Socio-Economic Consequences 2020 7032 https://doi.org/10.1051/shsconf/20219207032 with examining Industry 4.0.…”
Section: Theoretical Backgroundmentioning
confidence: 80%
“…In addition, their lack of interest and volition in relation to the training content might lead them to not listen to trainers, to miss some courses, and to not engage in several training tasks (Dysvik & Kuvaas, 2014), thereby limiting their engagement, learning, and satisfaction. In contrast, when trainees are autonomously motivated, they perceive their training program as more agreeable and stimulating and take pleasure during training, allowing them to better sustain continuous efforts, which in turn should allow them to experience more adaptive outcomes (Gillet et al, 2020).…”
Section: Outcomes Of the Motivation Trajectoriesmentioning
confidence: 98%